Determinants of Nyumba Kumi Community Policing Initiative on Maintenance of Law and Order in Migori County, Kenya - Owino, George; Moi, Edna (Journal of Public Policy and Administration, 2024)
Purpose: The study sought to determine the key factors influencing the success or failure of the Nyumba Kumi initiative in maintaining law and order within Suna West Sub-County, Migori County, Kenya. More specifically, it set out to explore how community awareness, collaboration with law enforcers, technology in use, and information sharing influence the success of this community policing endeavor. The study further points out difficulties inhibiting the success of this initiative, such as frayed relations between the community and police force, mistrust, and issues related to personal vendettas, which have undermined the initiative's goal of reducing insecurity. Methodology: This study utilized a descriptive cross-sectional research type to investigate the extent to which selected associated factors affected the implementation of the Nyumba Kumi initiative in Suna West Sub-County. Local community members, Nyumba Kumi leaders, and local administration officials were interviewed using structured questionnaires. A total sample of 210 respondents was represented from all key stakeholder groups using a stratified random sampling technique. Statistical analyses were performed to summarize variables of interest with the help of descriptive statistics like means, and standard deviations (SD) using SPSS version 26. The study also used inferential statistics (Pearson product-moment correlation) to examine the relationships between variables. Findings were tabulated and graphically displayed for trends and comparisons between indicators. Findings: The study achieved a high response rate, highlighting strong positive relationships between the maintenance of law and order and several key factors. Significant associations were found with community awareness (r = 0.759, p < 0.001), collaboration with law enforcement (r = 0.793, p < 0.001), technology use (r = 0.450, p < 0.001), and information sharing (r = 0.673, p < 0.001), all of which contributed to enhanced security in Suna West sub-county, Migori County. These findings indicate that the Nyumba Kumi initiative thrives on increased community awareness, effective collaboration with security agencies, and the integration of technology. Despite challenges such as strained relationships between community members and law enforcement, the initiative has led to reduced crime rates, quicker emergency response times, and more peaceful conflict resolution in the area. Unique Contribution to Theory, Practice and Policy: The study reinforces key theories related to community policing. It supports Collective Efficacy Theory by demonstrating how communities contribute to law and order through informal support and social control. It also bolsters Social Cohesion Theory, emphasizing the significance of strong social bonds for effective community policing. Furthermore, it validates social cognitive theory by illustrating how observational learning and social interactions influence community behavior in security initiatives. From a practical standpoint, the study recommends enhancing community training, fostering collaboration with law enforcement, integrating technologies such as mobile applications and GIS, and improving information sharing. These strategies serve as a practical framework for strengthening grassroots security efforts and enhancing the effectiveness of community policing within the Nyumba Kumi initiatives. Additionally, the study offers valuable policy recommendations that advocate for supporting community training, encouraging collaboration with law enforcement, promoting technology use, and enhancing information sharing. Implementing these policies would significantly improve community policing outcomes by facilitating better cooperation between communities and law enforcement agencies.